Navigating the implementation gap for Trastuzumab's journey from health insurance to patient access: a preliminary study in a hospital in China - Xingxia Yang; Yufei Jia; Jianhong Xu; Qin Zhou; Qian Long; Yi Yang; Yunguo Liu; Juanying Zhu; Xiaochen Zhang (Global Health Research and Policy)
Abstract Background Trastuzumab, a monoclonal antibody for breast cancer, faces global accessibility challenges, primarily due to high costs. This study examines how changes in medical insurance policies and price adjustments influence Trastuzumab utilization in China, focusing on implementation challenges and their impact on drug accessibility and affordability. Methods This retrospective study investigated Trastuzumab utilization among HER2-positive breast cancer patients at a tertiary hospital from May 2013 to December 2022 in JX, a prefecture-level city in eastern China. Patients were stratified based on their CerbB2 indicator, because those with a 2 + CerbB2 status require further FISH testing to confirm Trastuzumab eligibility. We analyzed the utilization rates of both FISH test and Trastuzumab using logistic regressions, identifying factors that influence their usage. Results 766 patients were included. The utilization rate of Trastuzumab among patients with CerbB2 3+ rose from 40.40 to 77.94% in September 2017 following the expansion of insurance coverage, and further increased to 90.41% after a price reduction in 2020. The FISH test was not covered by health insurance, and it was not available in the local hospital until Trastuzumab became available in JX city. For patients with CerbB2 2+, the proportion undergoing the FISH test increased dramatically from 8.89 to 82.08% after the price reduction in 2020. The mere inclusion into basic medical insurance, regardless of insurance types, significantly increased the utilization of Trastuzumab and the FISH test. However, rural patients in JX city are still facing financial burdens with Trastuzumab's out-of-pocket cost accounting for 62.9% of their annual disposable income in 2020. Conclusions Our findings indicate that insurance coverage and price reduction significantly increased Trastuzumab utilization. However, failure to improve the accessibility of the FISH test can pose challenges in enhancing the uptake of Trastuzumab among eligible patients. With the expiration of Trastuzumab's patent and the development of affordable biosimilars, there are now greater opportunities to enhance treatment access globally. These insights can inform policy makers of implementation guidance about providing financial support for breast cancer patients in other LMICs.